Assessment of surfactants on performance of molecularly imprinted polymer toward adsorption of pharmaceutical. Issue 2 (April 2019) - da Silva, Ricky Cássio Santos; Santos, Matheus Nishikawa; Pires, Bruna Carneiro; Dinali, Laíse Aparecida Fonseca; Suquila, Fabio Antonio Cajamarca; Tarley, César Ricardo Teixeira; Borges, Keyller Bastos
Graphical abstract: Abstract: Double imprinting process is fundamental to improvements in the adsorptive capacity of the molecularly imprinted polymers (MIP), but the effect of the surfactant type on adsorptive properties of the double-imprinted polymers are poorly understood. Thus, MIP to potassium diclofenac (PD) were developed and evaluated for their adsorbent properties. Polymers were characterized by infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetry (TGA) and textural properties. Kinetic studies performed at pH 6 showed the best fit ( R ² = 0.999) using a pseudo-second-order model. Adsorptive capacities toward PD of polymer using benzalkonium chloride (BC), sodium dodecylsulfate (SDS) and Triton X-100 (TT-X-100) were found to be 1.82 mg g −1, 1.12 mg g −1 and 0.51 mg g −1, respectively. MIP presented adsorptive capacity of 0.42 mg g −1, while for no template (NIP) 0.35 mg g −1 . Equilibrium adsorption data were best fitted with Freundlich isotherm for MIP-SDS, single-site Langmuir-Freundlich for MIP and dual-site for MIP-BC, MIP-TT-X-100 and NIP. Selectivity study proved that all the polymers had better binding capacity towards PD, with good selectivity and affinity over other drugs. This study showed that the addition of surfactant influenced the adsorbent properties of the material, being the MIP-BC the polymer with larger pore size, enhancing consequently the mass transfer of the DP toward the sorbent sites, so it presented better adsorption capacity.